2013
DOI: 10.7150/thno.5341
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Evaluation of the Effect of Repeated Administration and Clearance of Targeted Contrast Agents on Molecular Imaging Signal Enhancement

Abstract: Competitive inhibition diminishes ligand adhesion as receptor sites become occupied with competing ligands. It is unknown if this effect occurs in ultrasound molecular imaging studies where endothelial binding sites become occupied with adherent bubbles or bubble fragments. The goal of this pilot study was to assess the effect that repeated administration and clearance of targeted agents has on successive adhesion. Two groups of animals were imaged with 3-D ultrasonic molecular imaging. Injections and imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has also been reported that multiple injections of targeted MBs within 60 minutes do not block sufficient binding sites to bias molecular imaging data [34], which allows for imaging sessions with consecutive targeted MB injections. However, insonation of targeted MBs can reduce blood flow for up to 40 minutes with a frequency of 5 MHz and peak-negative pressure of 2 or 4 MPa [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that multiple injections of targeted MBs within 60 minutes do not block sufficient binding sites to bias molecular imaging data [34], which allows for imaging sessions with consecutive targeted MB injections. However, insonation of targeted MBs can reduce blood flow for up to 40 minutes with a frequency of 5 MHz and peak-negative pressure of 2 or 4 MPa [20].…”
Section: Discussionmentioning
confidence: 99%
“…Selective targeting is usually created by conjugating ligands, antibodies [14, 3540] or short peptides [20, 24, 25, 31, 4148] onto the surface of the contrast agent. Methods for conjugation include biological interaction (e.g., biotin-avidin [14, 20, 3540, 44, 45]) and covalent bonds [24, 25, 31, 34, 42, 4648]. The immunogenicity of short peptides is less than that of antibodies and is also reduced by covalent coupling rather than biotin-avidin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Streeter et al [176] performed 3D UMI of tumours expressing a v b 3 integrin by mechanically stepping the transducer across the tumour in 800 mm increments. In another study it was shown that multiple injections of tMBs did not block sufficient binding sites to bias molecular imaging data in serial studies [177], which is an important finding. Using the clinically promising BR55 agent, 3D UMI was shown to be very well suited in depicting the angiogenic activity in very small breast lesions, suggesting its potential for detecting and characterising these lesions at very early stages [178].…”
Section: Three Dimensional Umimentioning
confidence: 96%
“…Potential targeting ligands include antibodies [22, 5355], peptides [10, 26, 30, 31, 56], or engineered scaffold ligands [57, 58]. Methods to conjugate ligands onto the surface of contrast agents have included biotin-avidin coupling [22, 43, 5355] and covalent bonds [10, 26, 30, 56, 59]. In this paper, a peptide was displayed on the surface of the MB by including a lipo-PEG-peptide during self-assembly.…”
Section: Discussionmentioning
confidence: 99%